2021
DOI: 10.5114/reum.2021.108430
|View full text |Cite
|
Sign up to set email alerts
|

Bone-sparing effects of rituximab and body composition analysis in a cohort of postmenopausal women affected by rheumatoid arthritis – retrospective study

Abstract: Objective: Osteoporosis is the most common bone tissue disease and it is characterized by a reduced bone mineral density (BMD). The main physiopathological mechanisms converge on the uncoupling between bone formation and resorption, thus leading to an enhanced risk of fractures. Several papers have documented the inverse relationships linking high inflammatory cytokines, anticitrullinated protein antibodies, rheumatoid factor, and BMD in rheumatoid arthritis (RA). Rituximab (RTX) is a chimeric monoclonal antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
1
8
0
3
Order By: Relevance
“…After this process, 32 articles were included for the full-text screening. Finally, after the full-text reading, we included nine studies: Engvall et al [ 41 ] and Marcora et al [ 42 ] as randomized clinical trials and Al Khayyad et al [ 43 ], Vial et al [ 44 ], Tournadre et al [ 45 ], Toussirot et al [ 46 ], Ferraz-Amaro et al [ 47 ], Metsios et al [ 48 ], and Chikugo et al [ 34 ] as observational studies. The search and inclusion/exclusion criteria are described in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After this process, 32 articles were included for the full-text screening. Finally, after the full-text reading, we included nine studies: Engvall et al [ 41 ] and Marcora et al [ 42 ] as randomized clinical trials and Al Khayyad et al [ 43 ], Vial et al [ 44 ], Tournadre et al [ 45 ], Toussirot et al [ 46 ], Ferraz-Amaro et al [ 47 ], Metsios et al [ 48 ], and Chikugo et al [ 34 ] as observational studies. The search and inclusion/exclusion criteria are described in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of the nine studies included, four of them were performed in France [ 42 , 44 – 46 ], one of them in the UK [ 48 ], one in Spain [ 47 ], one in Japan [ 34 ], one in Sweden [ 41 ], and one in Italy [ 43 ]. Studies included were published between 2007 and 2020.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of bone resorption markers did not find any significant change after 12 months of Rituximab treatment [60]. A recent small retrospective study has found that after 18 months of RTX treatment the lumbar spine BMD has significantly improved in 20 postmenopausal women with RA (+ 7%, p = 0.0029), the femoral neck BMD remained stable [61]. These results suggest that studies with a longer observation period maybe required to detect a significant BMD change.…”
Section: Rituximab-minimal Bmd Changementioning
confidence: 92%